Faunal remains from Ojakly, a Late Bronze Age mobile pastoralist campsite in the Murghab region, Turkmenistan. (August 2022) - Rouse, Lynne M.; Woldekiros, Helina S.; Cerasetti, Barbara
Highlights: The first analyzed fauna related to a standalone Bronze Age campsite in Turkmenistan. Zooarchaeological data point to full-time caprine herding (sheep/goat) Meat and marrow consumption appears more important than secondary products. Use of cattle mainly restricted to irregular, non-food behaviors. Ojakly fauna presents a behavioral and consumption profile distinct from BMAC. Abstract: The publication of data relevant to prehistoric socio-economies in southern Central Asia is growing, and it intersects with long-standing questions about how mixed farming-herding subsistence economies were organized on local and regional scales. We present new faunal data from the campsite of Ojakly in south-central Turkmenistan, dated to the Late Bronze Age (1900–1500 BCE). We situate the zooarchaeological data within the site's overall excavation results and against similarly-contextualized fauna and archaeological remains from culturally-related sites, particularly those reported from the BMAC/Oxus site of Gonur-depe. Despite some overlaps in the domestic animal species utilized at Ojakly and at nearby farming-focused sites in the Murghab, there is a clear contrast in terms of the subsistence focus and practices, beyond what would be expected if these groups were specialized economic sub-sets of a single socio-cultural tradition. The faunal patterns at Ojakly are consistent with a pastoral population that exclusively managed mixed herds as a full-time subsistence strategy. The analysis presented here fits within the vein of identifying localized socio-economic adaptations of mobile pastoralists, especially as they blur traditional notions of "nomadic" and "farming" economies. At the same time, they add to larger datasets of temporal and regional relevance, and they are discussed within broader patterns known from published material.